2023
DOI: 10.1021/acsami.3c14766
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Gas Sensing Potential of Cross-Linked Asphaltene: A Promising Application of an Affordable Material

Mohamad-Anas Hejazi,
Salim Ok,
Jacob Samuel
et al.

Abstract: In recent years, there has been significant research interest in carbon-based nanomaterials as promising candidates for sensing technologies. Herein, we present the first utilization of asphaltenes as an affordable, cost-efficient carbon-based material for gas sensing applications. Asphaltenes, derived from various oil sources, are subjected to facile cross-linking reactions to produce nanoporous carbon materials, where the asphaltene molecules from different layers are interconnected via covalent bonds. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The heightened response observed in the cross-linked asphaltene samples was on par with that attained from graphene oxide (GO)-based sensor (Figure (a)). The improvement in sensing performance of the cross-linked asphaltenes was explained by their enhanced surface functionality and swelling capability, besides larger specific surface area and porosity . The QCM sensor utilizing cross-linked asphaltenes demonstrated an almost linear response, favorable response-recovery times, and outstanding response repeatability during cyclic exposure (Figure (b–d)).…”
Section: Applicationsmentioning
confidence: 95%
See 2 more Smart Citations
“…The heightened response observed in the cross-linked asphaltene samples was on par with that attained from graphene oxide (GO)-based sensor (Figure (a)). The improvement in sensing performance of the cross-linked asphaltenes was explained by their enhanced surface functionality and swelling capability, besides larger specific surface area and porosity . The QCM sensor utilizing cross-linked asphaltenes demonstrated an almost linear response, favorable response-recovery times, and outstanding response repeatability during cyclic exposure (Figure (b–d)).…”
Section: Applicationsmentioning
confidence: 95%
“…Although the studies mentioned above have emphasized the exceptional gas absorption capabilities of asphaltenes, their potential for application in gas sensing devices must still be explored. Very recently, Hejazi et al reported the first employment of asphaltenes in gas-sensing applications. They fabricated various quartz crystal microbalance (QCM) sensors with sensing films obtained from different raw and cross-linked asphaltene samples developed in the work of Ok and Samuel .…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation